ROAD TRAFFIC INDUCED ENVIRONMENTAL AIR CONDITIONS ON STREET-ENTREPRENEURS IN AKURE-SOUTH LGA. ONDO STATE, NIGERIA - Odesanya, Joseph Femi (2023)
Roadside corridor serves as a major hub for street entrepreneurs to display their items and carry out their business in most African city. The major objective of this research is to be carried out roadside analysis of the surrounding air along street corridor in other to determine the amount of Carbon monoxide (CO), Sulphur dioxide (SO2), Nitrogen dioxide (NO2) and Particulate Matter (PM10) which are by-product of automobile on the street entrepreneurs on the selected street in Akure, Ondo State, Nigeria. Likewise, both Survey and experiment analysis was deployed to obtain the real state of some of the common air pollutant in the corridor of study. Results shows that these informal entrepreneurs are greatly affected by road traffic air pollutant; as 12.45% of the respondents have high nasal discharge, 12.21% of the respondents reported high throat irritation, 12.21% of the respondents cough often, 4.72% reported high level of breathlessness and 4.11% reported high asthmatic condition. While it was observed that between 13.943ppm to 3.225ppm of carbon monoxide, 0.025 ppm to 0.007 ppm sulphur dioxide, 0.071 ppm to 0.016ppm of Nitrogen dioxide and 1156.000 µg/m3 to 328.260µg/m3 of Particulate matter 10 (PM10) is generated along the corridors of study. The study recommends that entrepreneurs in the informal sectors operating along road corridors should carry out their business at least 150m away from major road traffic path to avoid over exposure to automobile generated air pollutions as this will lead to a decrease in health hazard occasioned by over-exposure.